APPLICATION OF THE K-MEANS ALGORITHM IN IDENTIFYING TYPES OF SKIN DISEASE1 - Purwa Hasan Putra (INFOKUM, 2021)
In the process of grouping the types of skin diseases, doctors and hospital staff encountered various obstacles, including difficulties in grouping data on types of skin diseases. This analysis will assist the hospital in analyzing the data grouping of skin diseases. Data Mining Analysis using the K-Means algorithm for grouping types of skin diseases is an analysis used by doctors and hospital staff to determine grouping of patients based on the type of skin disease. By making this analysis, it is hoped that it can help hospital staff in classifying types of skin diseases